2007
DOI: 10.1097/01.ta.0000250599.84033.1f
|View full text |Cite
|
Sign up to set email alerts
|

The Anterolateral Thigh Flap is Highly Effective for Reconstruction of Complex Lower Extremity Trauma

Abstract: The ALT flap is a useful tool for trauma reconstruction in lower extremity salvage. We have shown that the ALT flap can be performed successfully in the traumatically injured patient even when harvested from the ipsilateral lower extremity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…15 Most studies of outcomes of lower extremity reconstruction with the ALT flap have focused on its use as a free flap for relatively distal defects. [16][17][18][19] The ALT flap has also been used as a pedicled flap for repair of more proximal lower extremity defects, though studies of this use often included patients with defects of the abdominal wall, perineum, and back. [20][21][22] In this study, we review our experience with the use of the ALT flap, in pedicled and free forms, for the repair of defects ranging from the hip to the foot.…”
mentioning
confidence: 99%
“…15 Most studies of outcomes of lower extremity reconstruction with the ALT flap have focused on its use as a free flap for relatively distal defects. [16][17][18][19] The ALT flap has also been used as a pedicled flap for repair of more proximal lower extremity defects, though studies of this use often included patients with defects of the abdominal wall, perineum, and back. [20][21][22] In this study, we review our experience with the use of the ALT flap, in pedicled and free forms, for the repair of defects ranging from the hip to the foot.…”
mentioning
confidence: 99%
“…It may be used for reconstruction of the chest wall (9), oropharynx (10-13), head and neck (14,15), hand (16)(17)(18), lower extremity (19)(20)(21), phallus (22) and abdominal wall (23). Use of the flap for breast reconstruction was originally described by Wei et al (1) …”
Section: Discussionmentioning
confidence: 99%
“…Koshima et al reported a potential surface area of 25  18 cm in the nonthinned flap, while others have more recently described success with flaps of up to 35 cm  15 cm. 1,3,7 The long vascular pedicle of the ALT flap ensures flap viability in the traumatic foot by allowing for microvascular anastomosis to a healthy recipient vessel located sufficiently far away from the site of injury. In a patient who has suffered an injury to his foot, the intrinsic thickness of the subcutaneous fat layer in the ALT flap is helpful and sometimes requisite for primary reconstruction and stabilization.…”
Section: Discussionmentioning
confidence: 99%